A case of mortality in suckling piglets due to pneumonia caused by Actinobacillus pleuropneumoniae. Issue 4 (12th October 2017) - Ustulin, Martina; Giorgiutti, Mirco; Conedera, Gabriella; Vio, Denis
Abstract : Two 7‐day‐old suckling piglets were submitted to the Diagnostic Laboratory of Pordenone of the Istituto Zooprofilattico Sperimentale delle Venezie (IZSVe) for pathomorphological examination. The piglets had died suddenly, showing blood‐stained discharge from nostrils and mouth, without any sign of crushing. Macroscopic examination revealed dark and solid pneumonic lesions in the diaphragmatic lobes associated with fibrinous pleurisy. Actinobacillus pleuropneumoniae was isolated from lesions; porcine reproductive and respiratory syndrome virus (PRRSV) was detected by RT‐PCR from the lungs. A pleuropneumoniae is a known cause of pneumonia and pleurisy in fattening and weaned pigs but, although colonisation of tonsils is well documented in suckling piglets, the clinical form of the disease in infant pigs has been infrequently described in endemically infected farms. Such events may be a consequence of the introduction of a new A pleuropneumoniae serovar, an incorrect gilt immunisation for this pathogen or inadequate colostrum intake by piglets.